PEMAHAMAN KARYAWAN PADA BUDAYA ORGANISASI DI PT. ABC MEDIUM DINAMIKA - Abdul Kholik (Jurnal Komunikasi dan Bisnis, 2019)
PT ABC Medium which was originally a stand-alone medium agency company, but after the company was acquired by a multinational company engaged in the medium sector. Since PT. ABC Medium joined and became part of this company, PT. ABC Medium is changing both in the organizational structure, work procedures and other regulations, therefore it is necessary to transform the culture of the company so that the behavior of its employees can adjust to the company's vision of becoming a global player. This study aims to determine employee understanding of old cultural values and employee understanding of the company's new cultural values. The research approach used is qualitative, with a constructivism paradigm, and the type of study is a case study. The results revealed that employees understood the value of the company's old culture as a culture of family, leadership, relaxed, bureaucratic, less competitive, client-oriented, competency-based. Employees understand the new culture of the company as a culture that has discipline values, rewards, and sacrifices, is efficient, based on competence, prioritizes education but lacks role models.Â Keywords: communication, organization, corporate culture